Identification of fertility restorer and sterility maintainer lines for diversified CMS lines in sunflower (Helianthus annuus L.): IDENTIFICATION OF FERTILITY RESTORER AND STERILITY LINES FOR CMS LINES IN SUNFLOWER - C NANDINI; Y G SHADAKSHARI; K T PUTTARANGASWAMY; K KARUNA (Journal of Oilseeds Research, 2018)
Six diversifiedCMS lines ARG-6-3-1-4, PKUZ, ARG-3, ARG-2-1-2, PRUN-29 and MUT2-8-3-2 were crossed with ninety six inbred lines in a line x tester fashion to study their sterility maintenance or fertility restoration reaction. Out of 96 inbreds tested, 48 inbreds restored fertility in the diversified CMS lines viz., ARG-6-3-1-4, PKUZ, ARG-3, ARG-2-1-2, while 47 and 45 inbreds restored fertility in MUT2-8-3-2 and PRUN-29, respectively. On the other hand, 39, 46, 45, 43, 44 and 46 inbreds maintained sterility in the diversified CMS lines ARG-6-3-1-4, MUT-2-8-2, PUKZ, ARG-3, PRUN-29 and ARG-2-1-2, respectively. Among 96 inbreds, as many as 38 inbreds were identified as common maintainers for all the six diverse CMS lines. Similarly, 39 inbreds were identified as common restorers for all the six diverse CMS lines. Effective restorer lines identified for alternate sources of cytoplasm could be exploited in developing hybrids with better heterosis and it can pave way for broadening the CMS sources used in commercial hybrid development. Identified promising maintainer lines could be used in development of new CMS lines through conversion.